Willingness to pay for vaccination against hepatitis b and its determinants: the case study of an industrial district of Pakistan (Epidemiology, Biostatistics, and Public Health, 2022)
Willingness to pay (WTP) for vaccination of hepatitis disease is a good measure to monetize the physical effects of a disease into monetary values. Therefore, the present study aims to find the willingness to pay for self-paid vaccines for hepatitis and its determinants in an industrial district Faisalabad, Pakistan. Primary data was collected from 200 nonpatients of hepatitis which were personally interviewed by using convenient sampling method.A scenario was presented to the selected respondents by using CVM technique. The respondents were randomly assigned to pre-chosen payment bids defined on the basis of prevailing market rates for vaccination at the time of survey. The multivariate linear regression was used to find the determinants of WTP. The results show that females are slightly more willing to pay as compared to males. The variables like age, income and awareness about hepatitis have positive impact on WTP for vaccination of hepatitis disease. About 57.3 percent people belonging to low income group wanted vaccination free of cost in Pakistan.Government should launch free vaccination programs for the most vulnerable group (poor) and must launch awareness campaign to increase knowledge about disease.